Pengembangan E-Commerce Berbasis CMS OpenCart untuk Meningkatkan Promosi Penjualan Makanan Ringan, Kopi dan Pembuatan Teralis Di Kecamatan Lembah Melintang - Atikah, Nur; Annas, Firdaus; Indra Cahyani, Yola (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The right promotional media is needed to increase sales of home-made products. The purpose of this study is to design an online promotional media using OpenCart that is easy and practical to use. Currently, the promotion of the sale of home-made UMKM products uses traditional promotional methods such as only displaying them in front of the house, so that the marketing reach is limited and not many people know about the home-made goods. In fact, the development of technology at this time provides a great opportunity for business actors to support home-made industry products to be widely known through online promotional media. This study uses the Research and Development (R&D) research method with the Define, Design, Develop, Decemination development model. The research process includes analysis of user needs, Designing an easy-to-understand interface, developing an OpenCart-based application, and user testing and evaluation to ensure that the application can meet the marketing needs of the business actor. The result of this study is an online promotional media using the OpenCart application that can be used by business owners to promote and introduce their products to the wider community.  From the results of this study, it was found that the OpenCart application is able to be the right promotional media to increase and facilitate online transactions for selling snacks and trellises made by home industries in Lembah Melintang District, West Pasaman.